2013
DOI: 10.1016/j.cortex.2012.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Item familiarity and controlled associative retrieval in Alzheimer's disease: An fMRI study

Abstract: Typical Alzheimer's disease (AD) is characterized by an impaired form of associative memory, recollection, that includes the controlled retrieval of associations. In contrast, familiarity-based memory for individual items may sometimes be preserved in the early stages of the disease. This is the first study that directly examines whole brain regional activity during one core aspect of the recollection function: associative controlled episodic retrieval (CER), contrasted to item familiarity in AD patients. Cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 137 publications
0
30
1
7
Order By: Relevance
“…In a previous fMRI study of memory retrieval in HC participants and AD patients, we found that despite lower recollection-based performance than HC participants, AD patients activated the PCC as HC participants. Connectivity analyses in this previous study revealed, however, that functional connectivity of the PCC during episodic retrieval was impaired in AD patients (Genon, Collette, Feyers et al, 2013). This suggests that brain functioning supporting recollection-related processes is complex and that impaired recollection function in AD patients might be related to subtle functional changes (probably in terms of connectivity) within a large-scale brain network.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 61%
See 2 more Smart Citations
“…In a previous fMRI study of memory retrieval in HC participants and AD patients, we found that despite lower recollection-based performance than HC participants, AD patients activated the PCC as HC participants. Connectivity analyses in this previous study revealed, however, that functional connectivity of the PCC during episodic retrieval was impaired in AD patients (Genon, Collette, Feyers et al, 2013). This suggests that brain functioning supporting recollection-related processes is complex and that impaired recollection function in AD patients might be related to subtle functional changes (probably in terms of connectivity) within a large-scale brain network.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 61%
“…Alzheimer's disease (AD) is characterized by impaired recollection-based processes, such as controlled retrieval (Knight, 1998;Smith and Knight, 2002;Adam et al, 2005;Genon, Collette, Feyers et al, 2013) and experience of remembering (Dalla Barba, 1997;Rauchs et al, 2007). In the same line, the quality of the recollective experience for autobiographical memories is impaired in AD patients (Irish, Hornberger, et al, 2011;Irish, Lawlor, et al, 2011;Piolino et al, 2003).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study (Genon et al, 2013), we found that AD patients showed activation of the PCC (which is assumed to be a crucial cortical hub in higher cognitive processes such as episodic memory retrieval (Leech and Sharp, 2014)) during episodic retrieval as healthy older participants did, while they showed 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 impaired functional connectivity between PCC on the one hand and hippocampus and lateral prefrontal cortex (LPFC) on the other hand. This suggested that impaired controlled/conscious retrieval of recent episodic memories in AD patients might be related to disconnection within a wide brain network.…”
Section: Discussionmentioning
confidence: 88%
“…One striking feature highlighted by previous fine examination of memory retrieval of recent memories in AD patients is the dissociation between automatic and controlled processes with the former being relatively preserved (based on familiarity or fluency for the memory trace) while controlled and conscious access to recently encountered information in memory (i.e. episodic memory retrieval) is particularly impaired (Dalla Barba, 1997;Genon et al, 2014;Genon et al, 2013). One relevant aspect that can be examined to better understand the neurocognitive mechanisms of episodic memory retrieval in AD is the insight or subjective judgment that the patients have on their current memory functioning when they are in the context of retrieving information from memory.…”
Section: Introductionmentioning
confidence: 99%